Cell–cell heterogeneity in phosphoenolpyruvate carboxylase biases early cell fate priming in Dictyostelium discoideum - Abe, Kenichi; Hashimura, Hidenori; Hiraoka, Haruka; Fujishiro, Shoko; Kameya, Narufumi; Taoka, Kazuteru; Kuwana, Satoshi; Fukuzawa, Masashi; Sawai, Satoshi (Frontiers in Cell and Developmental Biology, 2025)
Glucose metabolism is a key factor characterizing the cellular state during multicellular development. In metazoans, the metabolic state of undifferentiated cells correlates with growth/differentiation transition and cell fate determination. Notably, the cell fate of the Amoebozoa species Dictyostelium discoideum is biased by the presence of glucose and is also correlated with early differences in intracellular ATP. However, the relationship between early cell–cell heterogeneity, cell differentiation, and the metabolic state is unclear. To address the link between glucose metabolism and cell differentiation in D. discoideum, we studied the role of phosphoenolpyruvate carboxylase (PEPC), a key enzyme in the PEP-oxaloacetate-pyruvate node, a core junction that dictates the metabolic flux of glycolysis, the TCA cycle, and gluconeogenesis. We demonstrate that there is cell–cell heterogeneity in PEPC promoter activity in vegetative cells, which depends on nutrient conditions, and that cells with high PEPC promoter activity differentiate into spores. The PEPC null mutant exhibited an aberrantly high prestalk/prespore ratio, and the spore mass of the fruiting body was glassy and consisted of immature spores. Furthermore, the PEPC null mutant had high ATP levels and low mitochondrial membrane potential. Our results suggest the importance of cell–cell heterogeneity in the levels of metabolic enzymes during early cell fate priming.